HUKUMAN PIDANA KE KEADILAN RESTORATIF: REINTEGRASI SOSIAL DI BAWAH KERANGKA KERJA PERADILAN PIDANA BARU INDONESIA - Mashendra (Collegium Studiosum Journal, 2025)
This study aims to analyze the institutionalization of restorative justice in the new Criminal Code (Law No. 1 of 2023) and identify obstacles to its implementation in the criminal justice system. The method used is normative legal research with a qualitative approach through legislative, conceptual, and comparative analysis. Data was obtained from primary and secondary legal materials, while the analysis technique was carried out through doctrinal analysis and comparison with restorative practices in Europe and China. The results of the study show that although restorative justice has been recognized normatively, its implementation is still uneven among law enforcement agencies. The police tend to be more prepared than the prosecutor's office and the courts, which are constrained by a lack of human resources, training, and procedural guidelines. The lack of a trauma-informed and gender-responsive approach also limits victim participation. The study emphasizes the need for codification of restorative procedures, improved inter-agency coordination, and strengthening of community-based mechanisms to support effective implementation.